An Iterative Calibration Curve Procedure - Spiegelman, Clifford H. (J Res Natl Bur Stand (1977), 1984)
Calibration curves are an important part of many measurement processes. The user of a fitted calibration curve must know its precision and accuracy. These are determined in a timely fashion using the data iteratively. This paper gives a method that divides the data into training and test groups. The test group is iteratively checked to see that a prechosen nominal confidence interval probability of coverage is met. If on the basis of this check the calibration experiment is completed, the nominal probability level is shown to still be valid.